Apoyo emocional de la enfermera y depresión en el paciente hemodializado - hospital víctor lazarte echegaray - 2014 - González Vargas, Ada Belinda (2015)
This research descriptive - correlational, cross-sectional, was conducted during the months of July to December 2014, the Victor Lazarte Echegaray Hospital, in order to determine the relationship between the emotional support provided by the nurse and the degree of depression in haemodialysed patient. The sample consisted of 73 patients who met the inclusion criteria for data collection two instruments were used: Questionnaire to measure emotional support provided by nurses to patients on hemodialysis and Scale self-assessment for depression Zung . The data were tabulated and presented in graphs and statistical tables of double entry, numerical and percentage. The analysis of the relationship between the study variables was performed by testing the independence criteria "Chi Square". As a result we obtained the following conclusions: The 54.8 percent of patients received regulate emotional support; 28.8 percent were poor emotional support, and 16.4 percent received good emotional support. 50.7 percent of patients have moderate degree of depression, 27.4 percent have Leve degree of depression, 12.3 percent have a degree Intense Depression, and 9.6 percent have a normal degree of depression. Similarly 28.8 percent received regular emotional support and level of depression is moderate; 17.8 percent of patients received a poor emotional support and level of depression is severe; and 6.8 percent of patients received good emotional support and level of depression is normal. Thus, in applying the test of independence of criteria is evident that there is highly significant relationship between the degree of emotional support from the nurse and level of depression in haemodialysed patient, since the value of p is less than or equal to 0.005 (p ≤ 0005).